1998
DOI: 10.1086/301756
|View full text |Cite
|
Sign up to set email alerts
|

Splice-Site Mutations: A Novel Genetic Mechanism of Crigler-Najjar Syndrome Type 1

Abstract: Crigler-Najjar syndrome type 1 (CN-1) is a recessively inherited, potentially lethal disorder characterized by severe unconjugated hyperbilirubinemia resulting from deficiency of the hepatic enzyme bilirubin-UDP-glucuronosyltransferase. In all CN-1 patients studied, structural mutations in one of the five exons of the gene (UGT1A1) encoding the uridinediphosphoglucuronate glucuronosyltransferase (UGT) isoform bilirubin-UGT1 were implicated in the absence or inactivation of the enzyme. We report two patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…13). Many instances in which a single-base substitution at a splice junction resulted in abnormal splicing have been reported (3,14). Members of the TSU family (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13). Many instances in which a single-base substitution at a splice junction resulted in abnormal splicing have been reported (3,14). Members of the TSU family (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not immediately possible to conclude from the experiments in COS-7 cells that exactly the same aberrant mRNAs are being produced in the patient's hepatocytes, since cell-specific mRNA splicing of numerous genes, including the fibrinogen ␥-chain (FGG) gene, 20 has been proven, Gantla et al previously demonstrated the utility of the COS-7 model in evaluating the effects of potential splice-site mutations, particularly for genes expressed only in inaccessible tissues. 21 Two different outcomes were found for the common IVS4ϩ1GϾT mutation (cryptic splice-site activation) and the IVS3ϩ1_ϩ4delGTAA mutation (exon 3 skipping). Outcome of splice-site mutations in the fibrillar collagen genes COL1A1, COL1A2, COL3A1, and COL5A1 has been proposed to differ according to the order of intron removal.…”
Section: Discussionmentioning
confidence: 99%
“…The entire 2.2-kilobase pair mutagenized hUGT1A1 cDNA was excised by digestion with NotI and XhoI and subcloned into the pcDNA3.1/Zeo(ϩ) expression vector (Invitrogen). Introduction of the desired mutation was confirmed by nucleotide sequence determination by the dideoxy chain termination method (22)(23)(24).…”
Section: Sds-polyacrylamide Gel Electrophoresis Undermentioning
confidence: 99%
“…A 646-bp segment (nucleotides 320 -1066) was amplified by reverse transcription-primed polymerase chain reaction using the following amplimers: sense, 5Ј-GCGTGTGAT-CAAAACATACAA-3Ј; and antisense, 5Ј-GCCACTTAACAAGTATCGT-GTTG-3Ј. The sequence of the amplimer was determined by the dideoxy chain termination method using the cycle sequencing procedure as described (22)(23)(24).…”
Section: Sds-polyacrylamide Gel Electrophoresis Undermentioning
confidence: 99%